Exploring Happiness Management Practices in Czechia : A Case Study - Verma, Rupal; Pauknerová, Daniela, 1970-; Schmitt, Judith; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This bachelor thesis intends to explore happiness management implementations within an organization in Czechia and the challenges involved. The aim is to detail the tasks and responsibilities of happiness managers, what kinds of approaches to happiness management are utilized in the industry, and what kinds of challenges arise when implementing these methods. Semi-structured interviews were conducted with a representative of a selected company implementing happiness management practices in Czechia. The qualitative data collected from this practice was analyzed, and comparisons were made using existing literature to evaluate the company’s success with the implemented practices further. Conclusions were drawn to provide the organization with recommendations based on the results for enhancing the effectiveness of its practices. Along with this, the thesis makes practical contributions to furthering the development of happiness management based on the insights derived from this case study.
Vedoucí práce: Daniela Pauknerová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses